Characterisation of contrast agent microbubbles for ultrasound imaging and therapy research - Mulvana, H; Browning, R; Ling, Y; de Jong, N; Tang, M; Eckersley, R; Stride, E (Institute of Electrical and Electronics Engineers, 2016)
The high efficiency with which gas microbubbles can scatter ultrasound compared to the surrounding blood pool or tissues has led to their widespread employment as contrast agents in ultrasound imaging. In recent years their application has seen expansion from purely imaging to include the development of localised bio-effects for therapeutic applications and as agents to achieve super-resolution imaging. The growing exploitation of contrast agents in ultrasound, and in particular these recent developments, have amplified the need to characterise and fully understand microbubble behaviour. The aim in doing so is to more fully exploit their utility for both diagnostic imaging and potential future therapeutic applications. This paper presents the key characteristics of microbubbles that determine their efficacy in diagnostic and therapeutic applications and the corresponding techniques for their measurement. In each case we have presented information regarding the methods available and their respective strengths and limitations, with the aim of presenting information relevant to the selection of appropriate characterisation methods. First we examine methods for determining the physical properties of microbubble suspensions and the various light-scattering approaches for achieving this, then techniques for acoustic characterisation, both for microbubble suspensions and single entities. Where microbubbles are intended for use as therapeutic agents, potentially also acting as drug cargo carriers, detailed understanding of their surface characteristics and drug loading capacity is required. Finally we will discuss the attempts which have been made to allow comparison across the methods employed by various groups to characterise and describe their microbubble suspensions and promote wider discussion and comparison of microbubble behaviour.